Effect of melting rate on microsegregation and primary MC carbides in M2 high-speed steel during electroslag remelting - Fu-xing Yin (China Foundry, 2021)
Large-size primary MC carbides can significantly reduce the performance of M2 high-speed steel. To better control the morphology and size of primary MC carbides, the effect of melting rate on microsegregation and primary MC carbides of M2 steel during electroslag remelting was investigated. When the melting rate is decreased from 2 kg·min-1 to 0.8 kg·min-1, the columnar dendrites are gradually coarsened, and the extent of segregation of Mo and V is alleviated, while the segregation of Cr becomes severe. At 2 kg·min-1, the number of primary MC carbides per unit area with the sizes in the range of 2 μm to 6 μm accounts for about 75% of all MC carbides, while the carbides are mainly concentrated on the size larger than 8 μm at 0.8 kg·min-1. Thermodynamic calculations based on the Clyne-Kurz (simplified to C-K) model shows that MC carbide can be precipitated in the final solidification stage and a smaller secondary dendrite arm spacing caused by higher melting rate (2 kg·min-1 in this experiment) facilitates the refinement of primary MC carbides.